THREE-DIMENSIONAL RECONSTRUCTION BY SART METHOD WITH MINIMIZATION OF THE TOTAL VARIATION - S. A. Zolotarev; M. A. Mirzavand (Системный анализ и прикладная информатика)
Computed tomography is still being intensively studied and widely used to solve a number of industrial and medical applications. The algebraic reconstruction method with simultaneous iterations SART considered in this work as one of the most promising of iterative methods, suitable for the tomographic problems. Graphics processor is used to accelerate the speed of the reconstruction. The method of minimizing the total variation (TV) is used as a priori support for the regularization of the iterative process and to overcome the incompleteness of the information.